Gendered Labor Inequality and Policy Gaps: Indonesian Diaspora in Southern Philippines - Putri, Rara Gusnita; Munawaroh, Kholifatul (International Journal Administration, Business & Organization, 2025)
The phenomenon of cross-border migration between Indonesia and the Philippines, particularly in the Southern Mindanao region, has given rise to a significant Indonesian diaspora community. 65% of female migrant workers are undocumented, 80 cases of wage theft. However, this community often faces marginalization, especially in terms of access to fundamental labor rights and legal protection. This article analyzes the gender-based inequality experienced by Indonesian migrant workers, focusing on women employed in informal and domestic sectors groups that are particularly vulnerable to exploitation. The study examines public policy gaps at both national levels between Indonesia and the Philippines and the regional level, ASEAN. Highlighting the weak implementation of cross-border labor protections. Using a descriptive-analytical approach grounded in policy review and the theoretical framework of gendered labor, this article underscores the urgent need for inclusive, rights-based policy reform to promote fair and gender-responsive migration governance.